IDEA+ and OBFS: Using Transdisciplinary Strategies to Create More Inclusive Spaces - McDermott, Victoria; Roketenetz, Lara D; Jekielek, Phoebe; Struminger, Rhonda (Integrative and comparative biology, 2023)
Professional societies play a unique role in our personal and professional lives as spaces for connection and as regulatory entities. Often composed of volunteers from a variety of backgrounds, professional societies can guide the cultural norms and expectations of an industry by acting as critical leaders for supporting diversity, equity, and inclusion initiatives. The present manuscript explains how professional societies, like the Organization of Biological Field Stations (OBFS), can embrace transdisciplinary approaches to create more inclusive (in)tangible spaces to address serious problems facing industries today. Climate change, sexism, and racism, are examples of "wicked" problems that cannot be solved using existing modes of inquiry and decision making because of their complex and interrelated nature. As members of OBFS, a professional society dedicated to the advancement of field-based research, we explain how transdisciplinarity can and has been used to begin addressing serious issues like racism and sexism in field-based research and provide steps for future professional societies to engage in transdisciplinary thinking. We close with examples of our own transdisciplinary work developed through our membership within OBFS.